Clinical Epidemiology of Single Versus Multiple Substance Use Disorders: Polysubstance Use Disorder. Issue 9 (September 2017) - Bhalla, Ish P.; Stefanovics, Elina A.; Rosenheck, Robert A.
Abstract : Objective: While research on substance abuse has largely focused on people who have a single substance use disorder (SUD), many people abuse multiple substances. Studies have yet to examine the distinctive characteristics of patients diagnosed with more than 1 SUD and how those with polysubstance use disorder (PSUD) differ from those with a single SUD. Methods: National Veterans Health Administration data from fiscal year 2012 were used to compare veterans diagnosed 1 SUD to veterans diagnosed with 2–3, and >3 SUDs on demographic characteristics, psychiatric and medical diagnoses, medical and psychiatric service utilization, and psychotropic medication fills. Comparisons of the 3 groups were based on bivariate and multiple logistic regression analyses. Results: Of the 472, 624 veterans with at least 1 diagnosed SUD, 346, 329 (73.2%) had 1 disorder, 113, 598 (24.0%) had 2–3, and 12, 715 (2.7%) had >3 SUDs. Veterans with higher levels of PSUD were more likely to be black and homeless, were more likely to have hepatic disease as well as schizophrenia, bipolar disorder, major depressive disorder, and personality disorders. Higher levels of PSUD were associated with greater use of psychiatric inpatient care, residential and rehabilitative treatment, and with multiple psychotropic medication prescription fills. Conclusions: Veterans with PSUD have more severe problems along several dimensions and use more numerous and varied services than those with 1 SUD. This distinctive clinical profile warrants research to develop and evaluate methods for treating patients with complex multimorbid disorders that involve interactions between medical morbidity and psychosocial dysfunction.